The Influence of Taxpayers' Environment and Level of Trust On Taxpayer Compliance in Paying Land and Building Taxes in Nagori Tempel Jaya, Simalungun Regency - Eva Sriwiyanti; Wico J Tarigan; Misni Syafriani (Jurnal Ilmiah Accusi, 2025)
This study examines the influence of the Taxpayer Environment and the Taxpayer Confidence Level on Land and Building Tax (LBT) Compliance in Nagori Tempel Jaya. Using a quantitative approach, data were collected from 74 respondents owning land and/or buildings through questionnaires and structured interviews. Multiple linear regression analysis was employed to assess both partial and simultaneous effects. The results demonstrate that the model is statistically robust, with the F-test indicating a significant joint influence of both predictors on taxpayer compliance (F = 395.616; p < 0.001). The t-test further reveals that the Taxpayer Environment (t = 10.778; β = 0.699) and the Taxpayer Confidence Level (t = 4.474; β = 0.290) each exert significant partial effects. The coefficient of determination suggests exceptionally strong explanatory power (R² = 0.918), indicating that 91.8% of the variance in taxpayer compliance is explained by the two variables. The findings highlight that compliance is shaped by the combined influence of social norms, community dynamics, and institutional trust. This study provides empirical evidence relevant for local governments in enhancing taxpayer compliance through strengthened community engagement, improved transparency, and better-quality public services